PERILAKU IBU HAMIL DALAM MELAKUKAN PEMERIKSAAN KEHAMILAN PADA MASA PANDEMI COVID-19 DI PMB SURATMI - Dyka Aidina; Sarmauli Franshisca Sihombing; Tri Ribut Sulistiyawati (Universitas Batam, 2022)
In this COVID-19 pandemic situation, there are many restrictions to almost all routine services including maternal and neonatal health services. For example, pregnant women are reluctant to go to health centers or other health care facilities for fear of contracting them, the recommendation to postpone pregnancy examinations and classes of pregnant women. Lack of ANC visits can cause harm to both the mother and the fetus, such as bleeding during pregnancy because no danger signs are detected. The purpose of this study was to analyze the determinants related to the behavior of pregnant women in carrying out pregnancy examinations during the Covid 19 pandemic at PMB Midwives Suratmi. This study was conducted using an analytical survey method using a cross-sectional approach, the sample in this study was obtained the accidental method. A sampling of 45 trimester 3 pregnant women who did ANC. The results of the study using Chi-Square analysis showed that the value of P.<0.05 was that there was a significant relationship between the behavior of pregnant women doing ANC with age, education, knowledge, attitudes, and health facilities, the variables that were not related were the work of the mother and the support of the husband. 19 does not prevent pregnant women from doing routine prenatal checks.